OCD-FI: On-Chip Debug and Fault Injection - José Martins Ferreira (2006)
This paper presents a set of modifications to common processor on-chip debugging infrastructures to support the execution of fault injection campaigns. The proposed solution is applicable to different target architectures and imposes a very low logic overhead, providing a flexible and efficient mechanism for verifying and validating fault tolerant components.